Has Europeans always been better than Muslims in knowledge? - Akhmetova, Elmira (2018)
This paper discusses the scientific and educational developments during the eras of the Abbasid Caliphate and Muslim Spain. It suggests that Islamic civilisation played an important role in creating European civilisation, its values, systems, and progress.